Educational interventions are associated with improvements in colonoscopy quality indicators: a systematic review and meta-analysis - Causada-Calo, Natalia S.; Gonzalez-Moreno, Emmanuel I.; Bishay, Kirles; Shorr, Risa; Dube, Catherine; Heitman, Steven J.; Hilsden, Robert J.; Rostom, Alaa; Walsh, Catharine; Anderson, John T.; Keswani, Rajesh N.; Scaffidi, Michael A.; Grover, Samir C.; Forbes, Nauzer (Endoscopy International Open, 2020)
Background and study aims The quality of screening-related colonoscopy depends on several physician- and patient-related factors. Adenoma detection rate (ADR) varies considerably between endoscopists. Educational interventions aim to improve endoscopists’ ADRs, but their overall impact is uncertain. We aimed to assess whether there is an association between educational interventions and colonoscopy quality indicators.Methods A comprehensive search was performed through August 2019 for studies reporting any associations between educational interventions and any colonoscopy quality indicators. Our primary outcome of interest was ADR. Two authors assessed eligibility criteria and extracted data independently. Risk of bias was also assessed for included studies. Pooled rate ratios (RR) with 95 % confidence intervals (CI) were reported using DerSimonian and Laird random effects models.Results From 2,253 initial studies, eight were included in the meta-analysis for ADR, representing 86,008 colonoscopies. Educational interventions were associated with improvements in overall ADR (RR 1.29, 95 % CI 1.25 to 1.42, 95 % prediction interval 1.09 to 1.53) and proximal ADR (RR 1.39, 95 % CI 1.29 to 1.48), with borderline increases in withdrawal time, ([WT], mean difference 0.29 minutes, 95 % CI – 0.12 to 0.70 minutes). Educational interventions did not affect cecal intubation rate ([CIR], RR 1.01, 95 % CI 1.00 to 1.01). Heterogeneity was considerable across many of the analyses.Conclusions Educational interventions are associated with significant improvements in ADR, in particular, proximal ADR, and are not associated with improvements in WT or CIR. Educational interventions should be considered an important option in quality improvement programs aiming to optimize the performance of screening-related colonoscopy.